2018
DOI: 10.1155/2018/8234106
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Toughness and Hardness of Treated and Untreated Sisal Fibre‐Epoxy Resin Composites

Abstract: e effect of the combined chemical treatment of sisal fibres through the subsequent processes of mercerisation (alkali treatment), then silane treatment and eventually acid hydrolysis, on sisal fibre was investigated. e effect of the treated fibres on the impact toughness and hardness of their composites with epoxy resin was also studied. Scanning electron microscopy of the surfaces of the treated and untreated fibres showed that the chemical treatment processes enhanced the removal of surface impurities and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Enhanced wettability between chemically treated hemp fiber and epoxy resin is the possible reason for this improvement in microhardness properties of treated HFREC. [ 70 ] Comparing the tensile, impact, and microhardness properties of all the composites, the highest mechanical properties were obtained for PT HFREC followed by ST and UT HFREC.…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced wettability between chemically treated hemp fiber and epoxy resin is the possible reason for this improvement in microhardness properties of treated HFREC. [ 70 ] Comparing the tensile, impact, and microhardness properties of all the composites, the highest mechanical properties were obtained for PT HFREC followed by ST and UT HFREC.…”
Section: Resultsmentioning
confidence: 99%
“…In order to determine the impact properties of the fabricated composites, Charpy impact tests were performed at room temperature using a Hounsfield balanced impact tester, which imposes a three-point impact similar to that created by the Charpy apparatus specified in ASTM D6110-10 [16]. Test specimens with a geometry of 75 Â 8 Â 3.5 mm in length, width, and thickness, respectively, were cut from the cast composites.…”
Section: Impact Testsmentioning
confidence: 99%
“…It is observed that the potassium permanganate and MAPP treatments increased the storage modulus and loss modulus of treated composites at all ranges of temperatures as compared to the untreated ones. The works of Webo et al 47 combine the mercerisation of sisal fibres with subsequent silanisation in a 5% solution of (3-glycidyloxypropyl)trimethoxysilane. Following sufficient neutralisation and washing, it was found that the resultant fibres were more resistant to impacts, and the improvement in mechanical behaviour was higher than that obtained by performing these treatments individually.…”
Section: Characterisationmentioning
confidence: 99%
“…The untreated corn fibre sample showed the highest impact strength (7.00 kJ/m 2 ), whereas the sizing-treated samples possessed an impact strength of 6.00 kJ/m 2 . Webo et al 47 performed a Charpy test on treated and untreated samples of sisal fibre composites. At 50% weight fraction, the treated samples had an impact energy of about 13.00 J, which was marginally greater than the untreated sample's energy of 10.00 J. Venkatesh et al 77 evaluated the impact properties of sisal/bamboo hybrid composite.…”
Section: Characterisationmentioning
confidence: 99%
See 1 more Smart Citation